Conducting tests of hypotheses: the need for an adequate sample size - Mohd. Asraf, Ratnawati; Brewer, James K. (Springer Netherlands, 2004)
This article addresses the importance of obtaining a sample of an adequate size for the purpose of testing hypotheses. The logic underlying the requirement for a minimum sample size for hypothesis testing is discussed, as well as the criteria for determining it. Implications for researchers working with convenient samples of a fixed size are also considered, and suggestions are given about the steps that should be taken when they are not able to obtain a large enough sample. Finally, the implications of not having an adequate sample size for hypothesis testing are discussed to highlight the importance of determining sample size prior to conducting one’s study.